Three-dimensional numerical simulations of straight-bladed vertical axis tidal turbines investigating power output, torque ripple and mounting forces. (November 2015) - Marsh, Philip; Ranmuthugala, Dev; Penesis, Irene; Thomas, Giles
Abstract: Three straight-bladed vertical axis turbine designs were simulated using Three-Dimensional (3D) transient Computational Fluid Dynamics (CFD) models, using a commercial Unsteady Reynolds Averaged Navier–Stokes (URANS) solver. The turbine designs differed in support strut section, blade-strut joint design and strut location to evaluate their effect on power output, torque fluctuation levels and mounting forces. Simulations of power output were performed and validated against Experimental Fluid Dynamics (EFD), with results capturing the impacts of geometrical changes on turbine power output. Strut section and blade-strut joint design were determined to significantly influence total power output between the three turbine designs, with strut location having a smaller but still significant effect. Maximum torque fluctuations were found to occur around the rotation speed corresponding to maximum power output and fluctuation levels increased with overall turbine efficiency. Turbine mounting forces were also simulated and successfully validated against EFD results. Mounting forces aligned with the inflow increased with rotational rates, but plateaued due to reductions in shaft drag caused by rotation and blockage effects. Mounting forces perpendicular to the inflow were found to be 75% less than forces aligned with the inflow. High loading force fluctuations were found, with maximum values 40% greater than average forces. Highlights: Three straight-bladed turbine designs simulated using Computational Fluid Dynamics. Strut section, blade-strut joint design and strut location significantly impacted power output. Large torque fluctuations occurred around the rotation speed of maximum power. Turbine mounting forces were found to vary with turbine efficiency.